1975
DOI: 10.1128/jb.124.1.380-390.1975
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cyclic adenosine 3',5'-monophosphate and induction of tryptophanase in Escherichia coli

Abstract: The relationship between cyclic adenosine 3',5'-monophosphate (cyclic AMP) metabolism and the induction of tryptophanase and beta-galactosidase was studied in several strains of Escherichia coli grown with succinate, acetate, glycerol, or glucose as the carbon source. No consistent relationship between the intracellular concentration of cyclic AMP in the several strains cultured and the various carbon sources was discerned. In E. coli K-12-1 the induction of tryptophanase was found to vary in the order: succin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A comparison of the effect of cAMP on induction of tryptophanase and fi-galactosidase in E. coli showed that some combinations of carbon sources inhibited induction of tryptophanase while stimulating induction of ,B-galactosidase. It was proposed that control elements other than the CRP-cAMP complex respond to the catabolic situation in the cell and that these hypothetical control elements could control some but not all catabolic operons (24). It should be pointed out that catabolite repression occurs in some microorganisms, such as Bacillus megaterium, that contain no cAMP (255).…”
Section: Cyclic Nucleoti'des In Escherichia Coli and Salmonella Typhimentioning
confidence: 99%
“…A comparison of the effect of cAMP on induction of tryptophanase and fi-galactosidase in E. coli showed that some combinations of carbon sources inhibited induction of tryptophanase while stimulating induction of ,B-galactosidase. It was proposed that control elements other than the CRP-cAMP complex respond to the catabolic situation in the cell and that these hypothetical control elements could control some but not all catabolic operons (24). It should be pointed out that catabolite repression occurs in some microorganisms, such as Bacillus megaterium, that contain no cAMP (255).…”
Section: Cyclic Nucleoti'des In Escherichia Coli and Salmonella Typhimentioning
confidence: 99%
“…The regulatory protein, cAMP receptor protein (CRP), binds cAMP and causes the transcriptional activation or repression of many promoters [10]. The intracellular cAMP concentrations or the ability of the cell to accumulate cAMP are different in different nutrient compositions [11]. Early studies showed that changes in the dilution rate do not vary the cAMP level in E. coli , but this may be due to the technical difficulties of measuring low levels of cellular cAMP [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The cAMP-CRP complex makes up a positive-acting element required for efficient transcription initiation at catabolite-sensitive promoters; mutants deficient in CRP or adenylate cyclase are incapable of inducing the tna operon (reviewed in reference 16). However, other factors, independent of cAMP, probably also play significant roles in the catabolite repression of tna operon expression (10,11).…”
mentioning
confidence: 99%